2003
DOI: 10.1557/proc-791-q7.11
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Nanoscale Mechanical Properties of NiTi Shape Memory Alloy

Abstract: The mechanical properties of sputter-deposited NiTi shape memory alloy thin films ranging in thickness from 35 nm to 10 µm were examined using nanoindentation and atomic force microscopy (AFM). Indents made in films as thin as 150 nm showed partial shape recovery upon heating, although film thickness was found to have a marked effect on the results. A modified spherical cavity model is used to describe the findings, which suggest that the substrate tends block the shape memory effect as film thickness decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In fact, the latter is expected to play a significant role in the indentation response of SMAs, as this takes place in the indentation region due to the presence of highly localized stresses. As a consequence, well known contact mechanics theories for conventional metals cannot be directly applied to SMAs and work has been carried out, in recent years, to understand better the effects of microstructural transitions on the indentation response of both thin films [3][4][5][6][7][8] and bulk specimens [9][10][11][12][13][14][15]. These studies revealed marked effects of material composition, as well as the thermo-mechanical treatments carried out during material processing, on the indentation response of SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the latter is expected to play a significant role in the indentation response of SMAs, as this takes place in the indentation region due to the presence of highly localized stresses. As a consequence, well known contact mechanics theories for conventional metals cannot be directly applied to SMAs and work has been carried out, in recent years, to understand better the effects of microstructural transitions on the indentation response of both thin films [3][4][5][6][7][8] and bulk specimens [9][10][11][12][13][14][15]. These studies revealed marked effects of material composition, as well as the thermo-mechanical treatments carried out during material processing, on the indentation response of SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…NiTi possesses a series of interesting properties like ability to recover large transformation work, high actuation/weight ratio, shape recovery, damping capacity, chemical resistance, biocompatibility and pseudoelasticity (Fua et al 2004;Shaw and Crone 2004). Its microstructure and properties are, however, drastically sensitive to composition, thermomechanical treatment, heat evolution and prevailing stable and/or pseudo-stable phase presence (Busch and Johnson 1991;Ishida et al 1995;Zhang et al 2003;Ni et al 2005;Zhan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This technique provides a unique tool for studying the local mechanical properties as well as insight into the associated deformation mechanism in that scale [3]. The nanoindentation technique has been used for characterization of martensitic materials [4][5][6], but information of studies with bulk material is limited. However, even for a simple material structure, interpretation of load-displacement response is not a trivial task due to the complexity of stress field in the volume of material and the possible different deformation mechanisms, not to mention the complexity of the crystal structure or the effect of the possible special surface layers, such as oxides.…”
Section: Introductionmentioning
confidence: 99%